2018
DOI: 10.12962/j25796216.v1.i2.24
|View full text |Cite
|
Sign up to set email alerts
|

MPPT Control System Based on Incremental Conductance and Constant Voltage using Coupled Inductor-Capacitor Zeta Converter in hybrid PV-Wind Turbine System

Abstract: This paper proposes a method of maximum power point tracking control using Incremental Conductance employed in hybrid photovoltaic-wind turbine for DC micro-grid system. The rapid growth of renewable energy using photovoltaic (PV) and wind turbine due to low operational cost and easy to implementation. Improvement of the efficiency of PV and wind turbine based on incremental conductance is the solution to get maximum power in PV and Wind Turbine. The proposed method uses variable step to achieve maximum power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In [2], a well-formulated method is proposed for the commercial sizing of a grid-connected PV-wind hybrid energy system. Other contributions are made on their modeling and control techniques [7][8][9][10][11][12][13][14], but the majority of the proposed control schemes are based on the classical method, such as perturb and observe or incremental conductance algorithms and proportional-integral (PI) controller [7][8][9][10][11]. In reality, renewable energy generation systems are non-linear whereas the PI controller is designed for linear systems, and several comparative studies have already clearly demonstrated the moderate performance of this controller compared to non-linear controllers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In [2], a well-formulated method is proposed for the commercial sizing of a grid-connected PV-wind hybrid energy system. Other contributions are made on their modeling and control techniques [7][8][9][10][11][12][13][14], but the majority of the proposed control schemes are based on the classical method, such as perturb and observe or incremental conductance algorithms and proportional-integral (PI) controller [7][8][9][10][11]. In reality, renewable energy generation systems are non-linear whereas the PI controller is designed for linear systems, and several comparative studies have already clearly demonstrated the moderate performance of this controller compared to non-linear controllers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%